Innovaciones léxicos y literarias en la comedia palliata. ¿Cuestión de género o de autor? (Minerva, 2019)
In this work we carry out a study of the terms which contain a ‘deceit’ value in Terence’s comedy, and reach conclusions in comparison with the Plautus’ comedy.
Keywords: Plautus; Terence; Roman Comedy; deceit; genre; authorship